2011
DOI: 10.4103/2229-5186.90890
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of root of Alpinia galanga willd

Abstract: Objective: The objective of the study is to evaluate the acute and chronic anti-inflammatory activities of root extract of Alpinia galanga in rodents. Materials and Methods: The study was carried out using albino rats of either sex (150-200 g). An extract of the root of A. galanga was prepared using absolute alcohol and distillation in a Soxhlet apparatus. The acute anti-inflammatory effects of this extract were evaluated using carrageenan-, bradykinin-, and 5-HT-induced rat paw edema. The chronic anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…The eight isolated compounds (p-OH-benzaldehyde (1), trans-p-coumaryl-alcohol (2), p-coumaryl-aldehyde (4), galanganol A (5), galanganol B (6), trans-p-acetoxycinnamyl alcohol (7), 1′S-1′-acetoxychavicol acetate (9), and 1′S-1′-acetoxyeugenol acetate (10)) were identified by UHPLC-high-resolution Orbitrap ® mass spectrometry (HR-MS) and by NMR spectroscopy; the corresponding data is presented in the Supplementary Materials, while Figure 3 depicts the structures of the isolated compounds. In order to answer the questions raised about the possible conversion and decomposition of the A. galanga constituents during the PAMPA-BBB experiment, investigation of the chemical stability of the isolated compounds was carried out in PBS medium (pH 7.4) at 37 °C for 4 h. For the analysis of the samples acquired in the stability experiments, the aforementioned UHPLC-DAD method that had previously been validated for linearity, precision, and accuracy was utilized (Tables S1 and S2).…”
Section: Stability Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The eight isolated compounds (p-OH-benzaldehyde (1), trans-p-coumaryl-alcohol (2), p-coumaryl-aldehyde (4), galanganol A (5), galanganol B (6), trans-p-acetoxycinnamyl alcohol (7), 1′S-1′-acetoxychavicol acetate (9), and 1′S-1′-acetoxyeugenol acetate (10)) were identified by UHPLC-high-resolution Orbitrap ® mass spectrometry (HR-MS) and by NMR spectroscopy; the corresponding data is presented in the Supplementary Materials, while Figure 3 depicts the structures of the isolated compounds. In order to answer the questions raised about the possible conversion and decomposition of the A. galanga constituents during the PAMPA-BBB experiment, investigation of the chemical stability of the isolated compounds was carried out in PBS medium (pH 7.4) at 37 °C for 4 h. For the analysis of the samples acquired in the stability experiments, the aforementioned UHPLC-DAD method that had previously been validated for linearity, precision, and accuracy was utilized (Tables S1 and S2).…”
Section: Stability Analysesmentioning
confidence: 99%
“…The extracts of the rhizome as well as the two main phenylpropanoid constituents, 1 S-1 -acetoxychavicol acetate (ACA) and 1 S-1 -acetoxyeugenol acetate (AEA), have been reported to possess various biological activities [2]. A. galanga is known to have antimicrobial, antiallergic, and anti-diabetic activity and anti-inflammatory and gastroprotective effects [3][4][5][6][7][8]. Several recent studies with the major bioactive molecules suggested that the rhizome extract may have a potential neuroprotective effect, especially through inhibition of acetylcholinesterase enzyme activity, modulation of antioxidant markers, and nitric oxide (NO) production inhibitory activities [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to onset and duration of action, methanolic extract at 500mg/kg was comparable to ibuprofen. Ghosh et al 4 extracted AG twice with absolute alcohol and this extract was lyophilized. They further studied the extract of AG for anti-inflammatory effect using inflammation inducers like carrageenan, bradykinin and 5-HT in rats.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…18,19 It also shows excellent antimycobacterial, [20][21][22][23][24][25][26] anticancer, 20,21,[23][24][25][26][27] antifungal 20,[23][24][25][26][27][28][29] and anti-inflammatory activity. [23][24][25][26][27][28][29][30] It is reported that Akkermansia, which decreases mucin in the intestine, gets depleted in type 2 diabetes due to alteration in the gut microbes that lead to decreased insulin in the serum. 31 When Alpinia oil was administered, it decreased the blood glucose level and significantly reduced the damage caused to the renal pathology in type 2 diabetes mellitus.…”
Section: Alpinia Oxyphyllamentioning
confidence: 99%